2001
DOI: 10.1095/biolreprod65.1.188
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Characterization of the Cyclic Guanosine Monophosphate-Inhibited Phosphodiesterase PDE3A Expressed in Mouse Oocyte1

Abstract: In the preovulatory follicle, oocyte meiotic resumption occurs soon after the LH surge and is associated with a decrease in cAMP. Inhibition of cAMP degradation blocks germinal vesicle breakdown as well as activation of meiotic promoting factor, both hallmarks of reentry into the cell cycle. In situ and pharmacological analysis of rodent ovaries suggested the presence of a phosphodiesterase 3 (PDE3) in the germ cell but not the somatic cell compartment. Here we have investigated the structure and properties of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
58
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 32 publications
(44 reference statements)
6
58
0
Order By: Relevance
“…An attractive hypothesis is that LH stimulation leads to the activation of oocyte PDE, which hydrolyzes cAMP (Conti et al 2002). The PDE3A isoform is a prevalent PDE in the mouse oocyte (Tsafriri et al 1996, Shitsukawa et al 2001. PDE3A activity in cumulusenclosed mouse oocytes has been shown to increase following LH receptor stimulation ; however, PDE3A activity has not been examined in isolated oocytes following stimulation of the LH receptor.…”
Section: How Does Lh Trigger Meiotic Resumption?mentioning
confidence: 99%
“…An attractive hypothesis is that LH stimulation leads to the activation of oocyte PDE, which hydrolyzes cAMP (Conti et al 2002). The PDE3A isoform is a prevalent PDE in the mouse oocyte (Tsafriri et al 1996, Shitsukawa et al 2001. PDE3A activity in cumulusenclosed mouse oocytes has been shown to increase following LH receptor stimulation ; however, PDE3A activity has not been examined in isolated oocytes following stimulation of the LH receptor.…”
Section: How Does Lh Trigger Meiotic Resumption?mentioning
confidence: 99%
“…Phosphodiesterase (PDE) subtypes are differentially expressed in the somatic and germ cell compartments of the follicle (Tsafriri et al 1996, Park et al 2003. The oocyte-specific PDE that controls cyclic nucleotide accumulation is PDE type 3A (PDE3A) (Tsafriri et al 1996, Shitsukawa et al 2001. PDE3A is involved in in vitro induced and spontaneous resumption of meiosis in rat cumulus-enclosed oocytes (CEO): PDE3A activity is increased after stimulation by human chorionic gonadotrophin (hCG) and 2 h after oocyte isolation.…”
Section: Introductionmentioning
confidence: 99%
“…In both situations, this increase in PDE3A activity precedes oocyte nuclear maturation . Soluble forms of PDE3A exist in oocytes (Shitsukawa et al 2001), but the mechanisms of activation of the PDE3A remain unknown. Studies aiming to develop a new contraceptive strategy have shown that inhibition of PDE3A blocks oocyte meiosis in several species in vivo and in vitro (Tsafriri et al 1996, Wiersma et al 1998, Jensen et al 2002, Mayes & Sirard 2002, Nogueira et al 2003a.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 PDE3A, relatively highly expressed in mammalian oocytes, is the predominant PDE responsible for hydrolysis of oocyte cAMP. 13,14 Current thinking suggests that resumption of meiosis is triggered by LH, which increases cAMP and reduces cGMP in cumulus cells, leading to closure of gap junctions and decrease in oocyte cGMP. This relieves cGMP-induced inhibition RepoRt RepoRt Xenopus and human Cdc25C.…”
Section: Female Infertility In Pde3amentioning
confidence: 99%
“…1C) is most likely due to increased cAMP/PKA signaling which results from the absence of PDE3A, the predominant cAMP-hydrolyzing PDE in mouse oocytes. 13,14 We therefore compared PKA activities in WT and PDE3A -/-oocytes. As shown in Figure 2A, in the presence of excess cAMP (2 μM), total PKA activity is similar in lysates from fresh WT and PDE3A…”
Section: Genotyping As Seen Inmentioning
confidence: 99%